Vowel learning in diglossic settings: Evidence from Arabic-Greek learners. (February 2021) - Georgiou, Georgios P; Themistocleous, Charalambos
Aim and questions: Second language learners are often acquiring a second language (L2) in multilingual and bidialectal sociolinguistic environments. The competing pronunciations can be challenging to language learners. This study aims to determine the effects of language variety—standard variety versus local variety—on L2 vowel learning. Methodology: Vowel productions from 55 speakers were analyzed in the study; 10 speakers of Egyptian Arabic were recorded in a reading task producing Greek vowels and their vowel productions were compared to L1 vowel productions produced by 20 Standard Modern Greek and 25 Cypriot Greek speakers from a study by Themistocleous. Data and analysis: We conducted linear mixed effects models and tested the effects of language variety, vowel, and stress on the first and second formant frequency and on vowel duration. Findings: Egyptian Arabic speakers merge the middle Greek vowels /e/ and /o/ and the high /i/ and /u/ vowels. Also, they did not differentiate phonetically between L2 stressed and unstressed vowels. These findings are arguably an effect of the L1 vowel structure on L2 vowels. The two varieties exercised competing effects on learners' vowel productions, which suggests that both varieties are influencing vowel learning. Originality: There has been substantial research on L2 vowel learning in monolingual environments but not in diglossic environments; this study fills this gap by offering evidence about vowel learning in diglossic environments. Implications: In modern societies, communication takes place in multilingual environments. The findings highlight the impact of diglossia on L2 vowel learning and, ultimately, they demonstrate the importance of sociolinguistic factors on L2 learning.